Poverty Alleviation: Womenomics versus the Islamic Solution - Alvi Furwanti Alwie; Yeni Kusumawaty; Dina Hidayat (Perhimpunan Intelektual Muslim Indonesia, 2022)
Society currently faces problems in every aspect of life, including socioeconomic problems such as the problem of increasingly severe poverty. The Central Statistics Agency (BPS) report noted that the number of poor people in Indonesia in 2020 was 26.42 million. The existence of a pandemic exacerbates the situation with rising poverty levels. In addition, many women have to work as heads of households, and the high divorce rate makes the challenges even more difficult. One of the solutions to women's poverty that is currently the mainstream is the gender perspective. Based on this gender perspective, the idea of alleviating women's poverty was emerged through empowering women in the public sector, including in work environment. This idea has been supported by International Programs including the APEC Women and Economic Forum in early September 2013, which voiced the slogan 'Women as Economic Drivers'. In line with this, Japan also echoed the term womenomics. This article aims to: (1) identify the background of the emergence of the idea of womenomics and the extent to which it has been achieved; (2) identify the root cause of poverty and (3) recommend a complete solution to the problem of poverty from an Islamic perspective. The results show that the background of the push for women to public sector, including the womenomics strategy is not based on concern for women's welfare but as an instrument to pursue economic growth. So the results achieved are not far from the capitalist calculation. This womenomics perspective is in stark contrast to the view of Islam, where women and men have equal opportunities to achieve high rewards and positions before the Creator in their respective roles. The perfect Islamic Shari'a has a mechanism for solving people's poverty, and it has been proven during fourteen centuries of Islamic practice.